Fluorescein and OCT Angiography Features of Takayasu Disease. (4th July 2019) - Chotard, Géraldine; Diwo, Eleonore; Coscas, Florence; Butel, Nathalie; Saadoun, David; Bodaghi, Bahram
ABSTRACT: Purpose: Evaluate OCT (optical coherence tomography) angiography (OCTA) features in patients with Takayasau disease. Methods: The OCTA was analyzed to evaluate perifoveal anastomatic capillary arcade disruption, microaneurysms. The foveal avascular zone (FAZ) was measured for superficial (SCP) and deep capillary plexus. Results: There were 26 eyes included. In OCTA, 11 eyes presented ruptures of the perifoveal anastomotic capillary arcade in SCP. A total of 5 had microaneurysms. The average SCP FAZ was increased to 0.34 mm2 in Takayasu compared to 0.27 mm2 in control patients. Conclusion: Fluorescein angiography is the gold standard to describe Takayasu retinopathy ischemic signs. Macular abnormalities are uncommon in Takayasu patients as retinopathy signs are mostly located in peripheral retina. This study reveals that most of our patients present an enlargement of the FAZ then highlights the relevance of OCTA to evaluate macular ischemia as a complement to usual retina global study in fluorescein angiography.